2008
DOI: 10.1007/s11999-008-0177-8
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Squeaking in THAs with Alumina Ceramic-on-ceramic Bearings

Abstract: Ceramic-on-ceramic bearings in THA are a popular alternative to overcome wear concerns in traditional metal-polyethylene bearings. However, squeaking is a potentially worrisome phenomenon in ceramic-onceramic THAs which we observed in some of our patients. We reviewed all 42 patients who underwent 43 ceramicon-ceramic noncemented THAs during the time of the study. Squeaking, defined as a reproducible sound of squeaking, clicking, or grating, occurred in nine of 43 implants (20.9%). Standard radiographs were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
147
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(162 citation statements)
references
References 23 publications
7
147
1
3
Order By: Relevance
“…Five patients reported some transient noise (one squeak), but none underwent revision surgery for this problem. The proportion of patients reporting squeaking varies considerably, ranging from less than 1% to 20% [2,24]. In a prospective observational study of 1486 ceramic-on-ceramic THAs, 95 hips (6%) had squeaking develop [36].…”
Section: Discussionmentioning
confidence: 99%
“…Five patients reported some transient noise (one squeak), but none underwent revision surgery for this problem. The proportion of patients reporting squeaking varies considerably, ranging from less than 1% to 20% [2,24]. In a prospective observational study of 1486 ceramic-on-ceramic THAs, 95 hips (6%) had squeaking develop [36].…”
Section: Discussionmentioning
confidence: 99%
“…The Australian study also reported a higher variance in acetabular anteversion and inclination in the hips that squeaked. A study from The Netherlands reported a 20.9% incidence of squeaking in 43 noncemented COC hips [9]. That study reported no difference in patient characteristics or acetabular placement between squeaking and nonsqueaking hips, but found short necks on the implants in hips that squeaked.…”
Section: Introductionmentioning
confidence: 95%
“…That study reported no difference in patient characteristics or acetabular placement between squeaking and nonsqueaking hips, but found short necks on the implants in hips that squeaked. In three studies, squeaking reportedly developed an average of 14 to 26 months after surgery [9,11,16]. Although long-term clinical implications of squeak are unknown, the squeak phenomenon can have a psychological impact on patients, sometimes leading to decreased satisfaction or revision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the third-generation alumina ceramics have been shown to be superior to those with previous generations in terms of material properties and reducing risk of fractures [18], there still remains a number of concerns such as potential for ceramic fracture [13,21], noise issues [20], fewer intraoperative options and impingement [3], and decreased positional range of error during liner insertion [22]. These limitations of pure alumina characteristics required the development of improved ceramic materials.…”
Section: Introductionmentioning
confidence: 99%